The oxido-reductase enzyme glutathione peroxidase 4 (GPX4) governs Salmonella Typhimurium-induced neutrophil transepithelial migration - Agbor, Terence A (BlackWell Publishing Ltd, 2014)
Neutrophil (polymorphonuclear leucocytes; PMN) transmigration across mucosal surfaces contributes to dysfunction of epithelial barrier properties, a characteristic underlying many mucosal inflammatory diseases. Using Salmonella enterica serovar Typhimurium (S. Typhimurium) as a prototypic proinflammatory insult, we have previously reported that the eicosanoid hepoxilin A(3) (HXA(3)), an endogenous product of 12-lipoxygenase (12-LOX) activity, is secreted from the apical surface of the intestinal epithelium to establish a chemotactic gradient that guides PMN across the epithelial surface. Since little is known regarding the molecular mechanisms that regulate 12-LOX during S. Typhimurium infection, we investigated this pathway. We found that expression of phospholipid glutathione peroxidase (GPX4), which is known to have an inhibitory effect on 12-LOX activity, is significantly decreased at both the mRNA and protein level during infection with S. Typhimurium. Moreover, employing intestinal epithelial cell monolayers expressing siRNA against GPX4 mRNA, S. Typhimurium-induced PMN migration was significantly increased compared with the non-specific siRNA control cells. Conversely, in cells engineered to overexpress GPX4, S. Typhimurium-induced PMN migration was significantly decreased, which is consistent with the finding that partial depletion of GPX4 by RNAi resulted in a significant increase in HXA(3) secretion during S. Typhimurium infection. Mechanistically, although we found Salmonella entry not to be required for the induced decrease in GPX4, the secreted effector, SipA, which is known to induce epithelial responses leading to stimulation of HXA(3), governed the decrease in GPX4 in a process that does not lead to an overall increase in the levels of ROS. Taken together, these results suggest that S. Typhimurium induces apical secretion of HXA(3) by decreasing the expression of phospholipid GPX, which in turn leads to an increase in 12-LOX activity, and hence HXA(3) synthesis.